Three-jet events at the CERN intersecting storage rings - Angelis, A; Basini, G; Besch, H; Breedon, R; Camilleri, L; Chapin, T; Cool, R; Cox, P; Von Gagern, C; Grosso-Pilcher, C; Hanna, D; Humphries, B; et al. (1988)
Three-jet events have been observed in pp collisions at s = 62.3 GeV. The data were collected using a total neutral energy trigger with a threshold at 25 GeV. These events appear predominantly as two jets, with some appearing as three jets. A novel analysis for the extraction of 2-jet and 3-jet events is described, and some of the event properties are discussed. The relative numbers of two- and three-jet events are studied within the framework of leading-order QCD, and yield a value of αs(K3/K2) = 0.19 ± 0.02 (stat.) ± 0.04 (syst.). © 1988.